Pengaruh Kemampuan Hard Skill dan Soft Skill Terhadap Self Efficacy Mahasiswa (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The aims of this research are: 1). To determine the partial and simultaneous influence of Hard Skills and Soft Skills on Self-efficacy. 2). To determine the most dominant variables in forming student Self-Confidence (Self-efficacy). This research uses primary and secondary data. Primary data was obtained using questionnaires to 35 selected respondents and interviews, and secondary data was obtained from available literature. The analytical tools used are classical assumption tests, multiple linear regression analysis, and hypothesis testing. The research results show that Hard Skills (technical skills, science, technology) and Soft Skills (communication skills, emotional intelligence, thinking and problem-solving skills, ethics, and leadership skills) have a role in forming student Self-efficacy. Soft skills have the most dominant influence in realizing student Self-efficacy among the independent variables used. By having soft skills, students will be able to manage themselves well and correctly, so they will become individuals who have confidence in being able to carry out an activity well, able to obtain results as expected, able to manage their emotions well, able to be responsible and give accountability, and able to manage good relationships with each other.